If it's not what You are looking for type in the equation solver your own equation and let us solve it.
x in (-oo:+oo)
(63/4)*x^9 = 0
63/4*x^9 = 0 // : 63/4
x^9 = 0
x = 0
x = 0
| x/3+2-9/6+x/6-1 | | -5f-7+3.5=26.5 | | 6/7y+1/6(y-7)=y+1/7 | | 3x-5/10=7 | | 19+5/x=6 | | X+0.2x=24 | | 2y-3= | | 2.5(x+1)=1.5x | | 15.3=(-7.5k)+55.2 | | 0.7(6x+9)=3.4-(x-3) | | W/2.5=0.7 | | 2.33x+10+5.66x-9.5=12.5 | | 4x=8x+12x-16y | | M^2*m-30=0 | | 17(t-6)+4t=7(3t+4)-9 | | 2k^2-k-36= | | a/25=25 | | -5+8+-13= | | 2-4x=50 | | 0=x^4-29x^2-252 | | 2x-8+x=21 | | 2^(1/x)=0 | | 2^(1/x) | | 2/3x-2/3-2/5x+3/5-1 | | 2/x+3=5/2x+13/4 | | 7+3t-5=7t+10-3t | | 5+8+-13= | | 1.5x=15.17 | | 180=(x+3)+(2x-61) | | x-4.72=5.28 | | 7(t-4)+8t=5(3t+3)-11 | | 27-55= |